BREAKING BARRIERS: CHALLENGES IN DESIGNING ONLINE COMMUNICATION MODULE FOR INMATE REINTEGRATION - Januin, Junaidah; Atin, Veronica Petrus; Yakin, Halina Sendera Mohd; Tanalol, Siti Hasnah; Osman, Wan Hurani; Jawing, Esther; Matahir, Mohd Azri; Saimih, Abdul Halim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This paper explores the complex challenges encountered during the development and implementation of online communication modules within correctional facilities. Drawing upon insights from three module writers comprising lecturers at a public university and a prison officer in Sabah, Malaysia, the study meticulously examines the amalgamation of obstacles encountered in crafting effective online communication modules. Drawing upon insights from three module writers—two lecturers from a public university and a prison officer in Sabah, Malaysia—the study meticulously examines the amalgamation of obstacles involved in crafting effective online communication modules. Based on in-depth interviews and thematic analysis, three overarching themes emerge: Navigating the Labyrinth of Resource and Infrastructure Barriers, Training and Support, and Technical and Logistical Issues. By confronting these challenges and advocating for innovative, tailored solutions that are attuned to the unique demands of prison environments, correctional institutions can create meaningful educational opportunities that are pivotal for inmate rehabilitation and successful societal reintegration. The paper underscores the imperative for policymakers, educators, and practitioners to address these challenges with utmost attention, thereby prioritising education within correctional settings and empowering inmates through accessible and impactful online communication modules.